ISAU - A potential tropical longan (Dihocarpus longan) of Sarawak - Wong, K. C.; Yusof, Ibrahim; Pearce, K. G.; Alau Tayan, Douglas (1988)
The longan fruit, imported from Thailand, has been much sought by Malaysian. This fruit tree will not bear fruit under the tropical condition~ of the Malaysian lowland. However in Sarawak there is a variant of the longan known by the vernacular name of ISAU, the fruit of which possesses thick aril which tastes better than the imported longan. This paper describes some of the results of investigation on the taxonomy, botany, propagation and other aspects of exploitation of the Isau fruit carried out by the Bintulu Campus of Universiti Pertanian Malaysia.